The distant information interactions among people as the cosmophysical indicator of the intellect evolution on the Earth - Kaznacheev, Vlail; Trofimov, Alexander (Physics of Consciousness and Life, Cosmology and Astrophysics, 2006)
It is described the experimental results on the distant information interaction among people within the way of some thousands kilometers (Novosibirsk, Dikson, central Russia, West Europe, USA, Canada). During some experiments in the Extreme North it was revealed the “distant-time forestall” phenomena, i. e. the transmissed information reception by percipients, occurred some hours or days before its actual transmission. It was obtained the data about the dependence of the transmissed information reception on the cosmos situation during the prenatal period of the brain development as well as on the birthday date of the experiment participant.